Evaluation Of Xylazine-Ketamine And Xylazine - Acepromazine -Ketamine For Surgical Intervention In Mugger Crocodiles (Crocodylus Palustris) - Simon, Shiju; William, M. B. Justin; Jayaprakash, R. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The study was conducted in twelve crocodiles, divided into two groups of six each. Group I crocodiles were premedicated with xylazine @ 1.5 mg/kg and group II were premedicated using a combination of xylazine and acepromizine @ 1.5 mg/kg and 0.1 mg/kg body weight intramuscular respectively. In both the groups induction and maintenance were carried out by administering ketamine @ 20 mg/kg body weight intramuscularly. In this study, group II animals (xylazine- acepromazine with ketamine) provide excellent muscle relaxation, smooth induction and recovery. So this combination could be used for all major surgeries, xylazine and ketamine combination could be useful for minor procedures like translocation.